Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1785/0120200360
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Magnitudes from Dynamic Strain

Abstract: Dynamic strains have never played a role in determining local earthquake magnitudes, which are routinely set by displacement waveforms from seismic instrumentation (e.g., ML). We present a magnitude scale for local earthquakes based on broadband dynamic strain waveforms. This scale is derived from the peak root-mean-squared strains (A) in 4589 records of dynamic strain associated with 365 crustal earthquakes and 77 borehole strainmeters along the Pacific-North American plate boundary on the west coast of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The sensitivity required for a pair of GNSS antenna to discern strain signals of 100 nε would be a few mm with antennas separated by a few tens of km, prohibiting localizing the strain signals within several km of the source. Earthquake early warning (e.g., Barbour et al, 2021) may also be enhanced by this technology because an OFS is both a good seismometer and capable of rapid detection of large coseismic offsets; note also the large dynamic range accessible with this technology, covering six orders BSM). Spurious peaks from well-known electronic issues in the PBO BSM spectra near 0.084 and 0.042 Hz have been suppressed (see Barbour & Agnew, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity required for a pair of GNSS antenna to discern strain signals of 100 nε would be a few mm with antennas separated by a few tens of km, prohibiting localizing the strain signals within several km of the source. Earthquake early warning (e.g., Barbour et al, 2021) may also be enhanced by this technology because an OFS is both a good seismometer and capable of rapid detection of large coseismic offsets; note also the large dynamic range accessible with this technology, covering six orders BSM). Spurious peaks from well-known electronic issues in the PBO BSM spectra near 0.084 and 0.042 Hz have been suppressed (see Barbour & Agnew, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Strainmeters have the capability to record the whole spectrum of elastodynamic deformation (static and dynamic) [34] with little noise level, without saturation, and with no additional signal processing, and therefore show potential for EEW applications [82]. An earthquake magnitude scale based on local broadband dynamic strain waveforms has recently been developed by Barbour et al (2021) [85]. Its application to the 2019 M w 6.4 and 7.1 Ridgecrest earthquakes showed very promising results with magnitude estimates being in agreement to within about 0.3 magnitude units [85].…”
Section: Rapid Moment Magnitude Estimate and Implications For Eew Sys...mentioning
confidence: 99%
“…An earthquake magnitude scale based on local broadband dynamic strain waveforms has recently been developed by Barbour et al (2021) [85]. Its application to the 2019 M w 6.4 and 7.1 Ridgecrest earthquakes showed very promising results with magnitude estimates being in agreement to within about 0.3 magnitude units [85]. Therefore, the strainmeter networks may have a role to play in future EEW systems in Taiwan [86], provided a robust magnitude-scale calibration can be derived from past near-source large events (e.g., 2013 Ruisui, 2018 Hualien).…”
Section: Rapid Moment Magnitude Estimate and Implications For Eew Sys...mentioning
confidence: 99%
“…Numerous studies have shown that the borehole strainmeter can be used for seismic wave observation (Byerly, 1926;Johnston et al, 1986;Borcherdt and Glassmoyer, 1989;Borcherdt et al, 2006;Johnston et al, 2006;Blum et al, 2010;Barbour and Agnew, 2012;Qiu et al, 2015;Barbour and Crowell, 2017;Canitano et al, 2017;Cao et al, 2018;Farghal et al, 2020;Barbour et al, 2021). This initially realized seismologists' expectations of strain seismographs (Benioff et al, 1961;Aki and Richards, 2002).…”
Section: Introductionmentioning
confidence: 99%